Analysis of the Bullying: A Contribution from Latin American Scientific Production - Borja Villanueva, César Andrés (2020)
The study describes the characteristics of Latin American scientific production on the bullying variable in journals indexed in Scopus, during the period 2010-2018. A retrospective descriptive study is carried out analyzing 637 articles. It is found that the countries with the greatest production are Brazil, Chile, Mexico and Colombia. Most of the articles are published in the journals Science e Saude Coletiva y Psicologia Escolar e Educativo. 90.3% of the publications represent original articles. It is concluded that Latin American scientific production on bullying has been increasing progressively in recent years; However, it still represents a minimum percentage worldwide, it is necessary to continue strengthening the dissemination of scientific studies.